Adult multicentric burkitt lymphoma with bowel obstruction due to intussusception - Ali Özant; Kalbim Arslan; Necdet Özçay; Hasan Besim (Turkish Journal of Gastroenterology, 2019)
Primary malignant tumors of the small intestine are very rare, accounting for 2%-3% of all gastrointestinal malignancies. Lymphoma constitutes about 15%-20% of all small intestine neoplasms and 20%-30% of all primary gastrointestinal lymphomas. The ileum is the most common site for gastrointestinal lymphomas. Because the symptoms and physical findings are non-specific, the preoperative diagnosis is usually difficult. In this case report, we describe the highly unusual case of sporadic Burkitt lymphoma with complete intestinal obstruction due to intussusception of the proximal jejunum and discuss the treatment options. Cite this article as: Özant A, Arslan K, Özçay N, Besim H. Adult multicentric burkitt lymphoma with bowel obstruction due to intussusception. Turk J Gastroenterol 2018; 29: 361-4.